2016
DOI: 10.1128/msphere.00186-16
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasmid Type on the Replication of Rhodococcus equi in Host Macrophages

Abstract: This work greatly advances our understanding of the opportunistic pathogen Rhodococcus equi, a disease agent of animals and immunocompromised people. Clinical isolates from diseased foals carry a conjugative virulence plasmid, pVAPA1037, that expresses Vap proteins, including VapA, essential for intramacrophage replication and virulence in vivo. The understudied R. equi isolates from pigs carry a related but different plasmid, pVAPB, expressing distinct Vap proteins, including VapB. In this work, we document f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Previous work of our laboratory demonstrated that conjugal transfer of the 33705 pVAPB-type plasmid to the equine-derived pVAPA plasmid-cured 103S P- strain yielded a transconjugant (103S P- /A-p33705) that was able to replicate within murine and equine macrophages [ 20 ]. Those results indicated that the chromosome of an equine R .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work of our laboratory demonstrated that conjugal transfer of the 33705 pVAPB-type plasmid to the equine-derived pVAPA plasmid-cured 103S P- strain yielded a transconjugant (103S P- /A-p33705) that was able to replicate within murine and equine macrophages [ 20 ]. Those results indicated that the chromosome of an equine R .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, traditional lysis and plating of infected macrophage monolayers has a tendancy to under represent the total number of bacteria present in the monolayer. Thus, in this cell type, bacterial replication over time is followed by immunostaining infected monolayers and using fluorescent microscopy to enumerate the number of bacteria per 200 macrophages in triplicate at each time point [ 12 , 20 , 24 ]. In parallel, as an additional assessment, the number of macrophages with 10 or greater bacteria is recorded as previously described [ 12 , 20 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All R . equi strains found to be virulent for mice in laboratory conditions and pathogenic for foals contain the virulence plasmid, and the VapA protein is present in the cell [ 13 14 , 22 24 ]. Moreover, the absence of the plasmid or the VapA protein has been shown to be associated with the loss of virulence, although the presence of the VapA protein alone, without the other proteins of the family, does not enable the bacteria to multiply in murine macrophages or tissues or to colonize the lungs of experimentally infected foals [ 14 , 23 , 25 26 ].…”
Section: Introductionmentioning
confidence: 99%